Predictors of antenatal alcohol use among Australian women: a prospective cohort study. Issue 11 (17th July 2013) - Anderson, AE; Hure, AJ; Forder, P; Powers, JR; Kay‐Lambkin, FJ; Loxton, DJ
<x xml:space="preserve">Abstract</x> Objective To identify predictors of antenatal alcohol consumption among women who usually consume alcohol. Design Prospective cohort study. Setting Australian Longitudinal Study on Women's Health (ALSWH). Population or Sample A total of 1969 women sampled from the ALSWH 1973–78 cohort. Methods Women were included if they were pregnant in 2000, 2003, 2006 or 2009. The relationship between antenatal alcohol consumption and sociodemographics, reproductive health, mental health, physical health, health behaviours, alcohol guidelines and healthcare factors was investigated using a multivariate logistic regression model. Main outcome measures Alcohol use during pregnancy. Results Most (82.0%) women continued to drink alcohol during pregnancy. Women were more likely to drink alcohol during pregnancy if they had consumed alcohol on a weekly basis before pregnancy (odds ratio [OR] 1.47; 95% confidence interval [95% CI] 1.13–1.90), binge drank before pregnancy (OR 2.28; 95% CI 1.76–2.94), or if they were pregnant while alcohol guidelines recommended low alcohol versus abstinence (OR 1.60; 95% CI 1.26–2.03). Drinking during pregnancy was less likely if women had a Health Care Card (OR 0.63; 95% CI 0.45–0.88) or if they had ever had fertility problems (OR 0.64; 95% CI 0.48–0.86). Conclusions Most Australian women who drank alcohol continued to do so during pregnancy. Prepregnancy alcohol consumption was one of the main predictors of antenatal alcohol use. Alcohol guidelines, fertility problems and Health Care Card status also impacted antenatal alcohol consumption.